2006
DOI: 10.1002/pd.1542
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of congenital malformations and parental psychological distress-a prospective longitudinal cohort study

Abstract: Controlling for other covariates, we found that prenatal diagnosis of congenital malformations was a significant independent predictor of acute parental psychological distress after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 25 publications
8
109
1
2
Order By: Relevance
“…However, the existent studies showed that adjustment in the early post-diagnosis stage predicted parental adjustment in later evaluations (e.g., six months after the birth of the infant, Skari et al, 2006). Furthermore, even where there was a decrease in the levels of psychopathological symptoms over time, they tended to keep significantly higher than the normative values (Brisch et al, 2003;Brosig et al, 2007).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the existent studies showed that adjustment in the early post-diagnosis stage predicted parental adjustment in later evaluations (e.g., six months after the birth of the infant, Skari et al, 2006). Furthermore, even where there was a decrease in the levels of psychopathological symptoms over time, they tended to keep significantly higher than the normative values (Brisch et al, 2003;Brosig et al, 2007).…”
Section: Introductionmentioning
confidence: 86%
“…Finally, results also suggest that both fathers with high intensity emotional reactions at disclosure and mothers (regardless of their initial reactions) should be given particular attention, as they tend to present more adjustment difficulties in the early post-diagnosis stage, and, as such, are more prone to display a poorer adjustment in later evaluations (e.g., Skari et al, 2006). However, we should note that both emotional reactions at the disclosure and psychopathological symptoms should not be considered as indicators of maladjustment by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, a single session debriefing is standard clinical practice after traumatic events even if there is no consensus on whether a session debriefing can contribute to prevention of post traumatic stress disorder. 18,19 In our sample, communication of diagnosis was really sudden and unexpected without any previous suspicion of disease for 145 mothers and 76 fathers. This complies with the first APA criterion for trauma for which the subject has to experience the event as sudden and unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies of both mothers and fathers of infants born with a CA found that mothers presented higher levels of psychological distress than fathers (e.g., Pinelli et al, 2008;Skari et al, 2006) after the infant's birth, which may be explained by the mothers' primary role as caregivers (Hunfeld et al, 1999). However, other studies did not find gender differences in levels of psychological distress (Brosig et al, 2007).…”
Section: Psychological Distressmentioning
confidence: 73%
“…However, few studies have compared parental adjustment to the birth of an infant with a CA with the adjustment of parents of a healthy infant. Skari et al (2006) found that six weeks after birth, parents of infants with a surgically correctable CA had higher levels of psychological distress than parents of healthy infants. Comparing their data to normative data, Brosig, Whitstone, Frommelt, Frisbee, and Leuthner (2007) found that parents of children with congenital heart disease had higher levels of psychological distress at the time of their child's birth.…”
Section: Psychological Distressmentioning
confidence: 99%